2020
DOI: 10.31219/osf.io/sg8cm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computing sums in terms of beta, polygamma, and Gauss hypergeometric functions

Abstract: In the paper, by virtue of the binomial inversion formula, a general formula of higher order derivatives for a ratio of two differentiable function, and other techniques, the authors compute several sums in terms of the beta function and its partial derivatives, polygamma functions, the Gauss hypergeometric function, and a determinant. These results generalize known ones in combinatorics.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It is used in applied and engineering mathematics, statistics and probability, and computational physics. Recently, there is a great interest in the mathematical applications of beta function, some of these studies: [2][3][4][5][6][7][8][9]. Besides, in physics, the researchers observed that many properties of the strong nuclear force are defined by beta function, based on the data which are obtained during their research at CERN (The European Organization for Nuclear Research).…”
Section: Introductionmentioning
confidence: 99%
“…It is used in applied and engineering mathematics, statistics and probability, and computational physics. Recently, there is a great interest in the mathematical applications of beta function, some of these studies: [2][3][4][5][6][7][8][9]. Besides, in physics, the researchers observed that many properties of the strong nuclear force are defined by beta function, based on the data which are obtained during their research at CERN (The European Organization for Nuclear Research).…”
Section: Introductionmentioning
confidence: 99%